2009
DOI: 10.1016/j.resp.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The compensatory responses to upper airway obstruction in normal subjects under propofol anesthesia

Abstract: Upper airway obstruction during sleep can trigger compensatory neuromuscular responses and/or prolong inspiration in order to maintain adequate minute ventilation. The aim of this study was to investigate the strength of these compensatory responses during upper airway obstruction during propofol anesthesia. We assessed respiratory timing and upper airway responses to decreases in nasal pressure in nine propofol anesthetized normal subjects under condition of decreased (passive) and increased (active) neuromus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
1
34
0
1
Order By: Relevance
“…In allergen sensitized and challenged mice Ti and PIF are primarily influenced by extrapleural obstructions and are typically elevated with Mch challenge when an obstruction exists. 25, 26 The Asthma and Dex-Asthma mice showed . Each value is the mean Ϯ SEM for n ϭ 8.…”
Section: Respiratory Parametersmentioning
confidence: 99%
“…In allergen sensitized and challenged mice Ti and PIF are primarily influenced by extrapleural obstructions and are typically elevated with Mch challenge when an obstruction exists. 25, 26 The Asthma and Dex-Asthma mice showed . Each value is the mean Ϯ SEM for n ϭ 8.…”
Section: Respiratory Parametersmentioning
confidence: 99%
“…Nonetheless, compared to isoflurane, where already 0.4 MAC, which is light sedation and comparable to a propofol plasma level of 1.0 μg/mL, caused significant upper airway collapse and complete depression of phasic genioglossus EMG activity (158), propofol seems to have a greater safety margin. As described earlier in this section Hoshino et al (279) showed that propofol increased upper airway collapsibility as measured by critical opening pressures to a similar degree as natural non-REM sleep.…”
Section: Effects On Upper Airway Musclesmentioning
confidence: 54%
“…Two compensatory mechanisms can be induced in an attempt to maintain desired ventilation during partial airway obstruction with a consequent increase in inspiratory upper airway resistance: (1) Increase inspiratory muscle pressure or effort (i.e. increasing the work of breathing) (Badr et al, 1990;Younes and Riddle, 1981); and (2) increase the duty cycle of the inspiratory portion of the breath to maintain an equal tidal volume despite a reduced peak flow (Hoshino et al, 2009;Poon, 1989). The latter has been quantified by calculating the fractional inspiratory time (Jordan et al, 2007;Schneider et al, 2003); with the increase in the inspiratory period presumed to be associated with a reduced expiratory period (Onal and Lopata, 1986).…”
Section: Introductionmentioning
confidence: 99%